2014
DOI: 10.5897/jvmah2013.0229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the newcastle disease antibody level after vaccination regimes in chickens in Debrezeit Agricultural Research Center, Ethiopia

Abstract: Evaluation of the Newcastle disease (NCD) antibody level after different vaccination regime was conducted on 110 chickens: (32%) vaccinated and kept separated, (25.2%) unvaccinated and kept with vaccinated, (25.2%) were control groups. Four vaccination regime of chicken against NCD using live lentogenic stain, Hithcner B1 (at the age of 3 day old) and lasota (at the age of 27, 63, and 112th days of age) were used. The overall antibody level of ND in examined chickens using HI test was Log 2 4.42 in unvaccinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Compared to the standard schedule used in Ethiopia, this approach provided superior protection against the virulent ND virus, enhancing layer chicken immunity through eye-administered live virus vaccines. Anebo et al (2014) reported similar findings, stating that the new immunization method provided protective immunity that was comparable to the conventional approaches employed in Ethiopia.…”
Section: Ta B L Esupporting
confidence: 56%
See 2 more Smart Citations
“…Compared to the standard schedule used in Ethiopia, this approach provided superior protection against the virulent ND virus, enhancing layer chicken immunity through eye-administered live virus vaccines. Anebo et al (2014) reported similar findings, stating that the new immunization method provided protective immunity that was comparable to the conventional approaches employed in Ethiopia.…”
Section: Ta B L Esupporting
confidence: 56%
“…Anebo et al. (2014) reported similar findings, stating that the new immunization method provided protective immunity that was comparable to the conventional approaches employed in Ethiopia. Furthermore, several studies (Kapczynski et al., 2013; Sedeik et al., 2019; Sedeik et al., 2022) have suggested that vaccination programs employing a progressive strategy, which involves successive booster immunizations with increasingly virulent strains, could offer protection against clinical disease and mortality following infection with virulent NDV.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Newcastle disease is a highly contagious and commonly fatal viral poultry disease affecting domesticated and wild avian species 4 . The disease affects birds of all ages.…”
Section: Introductionmentioning
confidence: 99%
“…However, chicken production is constrained by the disease, predation, lack of management and appropriate breeds in the country (Tadiose et al, 2016); (Terfa et al, 2018)). Among these constraints, disease is the most important and responsible for reducing both numbers and productivity, mortality from egg to adult because of the disease can be estimated to be 80% during some spectacular epidemics (Kinung'hi et al, 2004); Zelalem et al (2014). Different poultry disease has been reported in Ethiopia, the major cause of economic losses being Newcastle disease (ND), coccidiosis, chronic respiratory disease, Marek's disease, Nutritional deficiencies (Lobago et al, 2005;Mesfin and Bihonegn, 2018).…”
mentioning
confidence: 99%